Georgiy Gachev as a researcher of the Turkic world - Kuchukova, Zukhra A.; Bauaev, Kazim K.; Berberova, Liana B. (The New Research of Tuva, 2024)
The purpose of this article is to analyze the Turkic pages of the ethnological ‘encyclopedia’ written by the Russian scholar G. D. Gachev in his works on national images of the world. The authors examined the Kazakh, Kyrgyz, Azerbaijani, and Karachay-Balkarian ethnic groups as described in Gachev’s works and in those developed by his students — ethnophores from these regions. The analysis is based on Gachev’s writings and the memoirs of his colleagues. Using the method of component analysis, the authors identified a “Turkic tree” and then examined several subethnic “branches” of this tree. It is concluded that the “Gachev and Turkic World” tandem is a vast, independent, and fascinating field of humanities. This tandem highlights the scope of Gachev’s ethnographic and cultural expertise and allows for a clear identification of the distinctive features of each Turkic ethnic group.